Increasing access to psychological services within pediatric rheumatology care - Alana Goldstein-Leever; Christine Bearer; Vidya Sivaraman; Shoghik Akoghlanian; James Gallup; Stacy Ardoin (BMC, 2023)
Abstract Background Given the impact of psychological factors on rheumatic disease, pediatric psychologists serve a vital role in promoting quality of life and managing common problems among youth with rheumatic disease. The aim of this project was to increase access to psychological services among youth with rheumatic disease at a children's hospital. Methods A quality improvement (QI) team identified key drivers and interventions aimed to increase access to psychological services for youth with rheumatic disease. Data was collected for a 6-month baseline period and 4-year intervention period. We applied the Plan-Do-Study Act method of QI and the American Society for Quality criteria to adjust the center line and control limits. Results There were two statistically significant center line shifts in the number of patients seen by psychology and one statistically significant shift in referrals to psychology over time with applied stepwise interventions. Patients seen by a psychologist increased by 3,173% from a baseline average of 1.8 to 59.9 patients seen per month (p < 0.03). Psychology referrals increased by 48% from a baseline average of 9.85 to 14.58 referrals per month over the intervention period (p < .01). Conclusions Youth with rheumatic disease received increased access to mental health treatment when psychological services were imbedded within rheumatology care. Psychology referrals also increased significantly, suggesting that psychology integration within a medical clinic can increase identification of needs. Results suggest that psychology integration into rheumatology care may increase access to mental health treatment and identification of psychological needs in this at-risk population.